In Search of Transformative Learning for Sustainable Development: Bibliometric Analysis of Recent Scientific Production - Varela-Losada, Mercedes; Pérez-Rodríguez, Uxío; Lorenzo-Rial, María A.; Vega-Marcote, Pedro (Frontiers in Education, 2022)
Transformative learning is a key element when it comes to making progress towards sustainable development. This goal requires an education that fosters the empowerment of people and the transformation of institutions, prepares for the necessary changes, facilitates resilience and encourages sustainable actions. The aim of this paper is to review the academic production on transformative learning in relation to the pursuit of sustainable development. To do so, a bibliometric analysis was conducted of the publications included in the Scopus databases for the 2003-2020 period, in order to explore its evolution, identify the main themes of which the field of knowledge is composed, and identify its main references and the network of collaborations between researchers and universities worldwide. During this period, scientific production has increased considerably, with a particular focus on adult education and competency development. At the same time, English-speaking dominance and the prevalence of Western origin has been observed. There is a need for more global, connected, and pluralistic research that is focused on diverse sociocultural contexts, research that factors in inequality and environmental justice and which calls into question the current socioeconomic model. A debate should also be started on which means of publication are the most appropriate for defending the quest for sustainability.